Are Czechs interested in employment in forestry? - Abramuszkinová Pavlíková, Eva; Stachová, Jana; Somerlíková, Kristina; Svobodová, Eliška; Šilhan, Zdeněk; Holušová, Kateřina (Česká akademie zemědělských věd, 2026)
This study analyses the professional interests and motivations of people regarding forestry careers. An online survey (N = 162) was conducted in May 2025. The study identifies the profile of a typical forestry candidate as an individual from a rural area, regardless of gender, who prioritises job security and personal satisfaction over high financial reward. The findings confirm that while forestry students show the strongest interest, intrinsic motivation and a personal relationship with nature are the primary drivers across the board. The key results indicate that practical field experience and communication with professionals significantly bolster career interest. Furthermore, the emerging generation of foresters demonstrates an 'ecologically realistic' perspective, favouring sustainable management and biocentric values over traditional paradigms. The study suggests that to combat the declining workforce, forestry communication should leverage these intrinsic values and increase practical engagement during university studies. Respondents assigned the greatest importance to statements reflecting biocentric and ecocentric values, emphasising the intrinsic value of forests, ecosystem impact considerations, and their role in environmental balance and human well-being.
Keywords: attitude; career; motivation; values; well-being